A Chinese EFL Teacher's Classroom Assessment Practices. Issue 4 (2nd October 2017) - Wang, Xiaoying
ABSTRACT: This article reports on a case study of how an experienced EFL teacher assessed her students in her oral English course at a university in China. Data were collected over one semester through document analysis, classroom observation and recording, interviews, and student journals. Analysis revealed that the teacher assessed her students through both summative assessment (SA) and formative assessment (FA), with some assessment practices serving both formative and summative purposes simultaneously (dual-purpose CA). Moreover, the teacher integrated her FA and SA in a productive way that pushed her students to make progress in an upward spiral. The article ends with a recommendation that experienced teachers' expertise on classroom assessment should be revealed and described, which may help teachers bridge the gap between assessment theories and classroom practices.